Resenha: Globalizing music education: a framework (Alexandra Kertz-Welzel, 2018) (Orfeu, 2019)
This text presents the review of the book “Globalizing music education: a framework” by german researcher Alexandra Kertz-Welzel (2018), professor at Ludwig-Maximilians-Universität München (LMU). The book’s main subject is the globalization and internationalization in the field of Music Education, bringing reflections on practices, policies and research to propose a conceptual field aimed at strengthening an international community of culturally sensitive musical education.
Keywords: globalization; internationalization; Music Education